Community-Based Panyaweuan Tourism Attraction Development Strategy in Majalengka Regency - Wibowo, Riyanto; Wibowo, Toni Ari; Fitriyana, Dian (Ann Publisher, 2025)
Background. Panyaweuan tourist attraction. This tourist object is situated in Argapura, within Argamukti Village, Argapura District, Majalengka Regency, West Java, and is an excellent attraction for development. However, the Panyaweuan tourist object still offers minimal tourist attractions (attractions), accessibility (accessibility), facilities (facilities) of tourism institutions (ancillary), and community involvement (community involvement). Hence, it needs to identify potential tourist attractions. Purpose. Formulating a development strategy for Panyaweuan tourist attractions in Argamukti village, Argapura District, Majalengka regency, Method. This research was conducted at the Panyaweuan tourist attraction in Argamukti village, Argapura district, Majalengka Regency. It is a field research study involving observations, interviews, and documentation for data collection. Result. The results of data collection from observations, interviews, and documentation are described in accordance with the current conditions and circumstances. The results of describing potential objects and tourist attractions at the Panyaweuan tourist site in Argamukti village, Argapura district, Majalengka Regency, will be analyzed using SWOT analysis. Then, the priority strategy analysis will be carried out based on Internal Strategy Factors (IFE = Internal Factors Evaluation) and External Strategic Factors (EFE = External Factors Evaluation) in the development of tourism as a tourist destination. Conclusion. The tourism development strategy in the Panyaweuan tourist attraction of Tejamulya village is an agro-tourism-based tourism by looking at the potential in the form of natural beauty, the potential of agricultural and plantation products, supported by products produced by the community in the Panyaweuan area, so that it can provide economic benefits to the local community. However, Panyaweuan must enhance its supporting facilities to ensure visitor comfort and satisfaction. Additionally, all activities parwisata must be community-based with technological readiness (TKT) 3 and will be published in the Udayana-Bali tourism journal.